SAE Technical Paper Series 2019
DOI: 10.4271/2019-01-1303
|View full text |Cite
|
Sign up to set email alerts
|

Model Based Control of Synchronizers for Reducing Impacts during Sleeve to Gear Engagement

Abstract: his paper presents a model based control strategy aimed to reduce noise and wear during gearshifts in conventional and hybrid Dual Clutch Transmissions (DCT and DCTH) and Automated Manual Transmissions (AMT). The control strategy is based on a newly developed dog teeth position sensor layout at China Euro Vehicle Technology AB (CEVT), a detailed simulation model for gear engagement and already existing speed sensors in the transmission. The details of dog teeth position sensor and simulation model are also pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(20 citation statements)
references
References 7 publications
0
20
0
Order By: Relevance
“…T s can be provided either by synchronizer ring or by electric motor as explained by [7]. Maximum value of synchronization torque T s provided by either source is denoted by T max , so The rotational dynamics of the idler gear can be written as…”
Section: Speed Synchronizationmentioning
confidence: 99%
See 4 more Smart Citations
“…T s can be provided either by synchronizer ring or by electric motor as explained by [7]. Maximum value of synchronization torque T s provided by either source is denoted by T max , so The rotational dynamics of the idler gear can be written as…”
Section: Speed Synchronizationmentioning
confidence: 99%
“…A lot of research has been done on dynamic modeling of these impacts as shown in [5] and [6]. [7] shows research on control system development to avoid these impacts altogether. In order to avoid the dog teeth impacts, "Dog Teeth Position Sensor" mentioned in [7] is needed .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations